Pengaruh Cyberloafing dan Stress Kerja terhadap Kinerja Karyawan Pada Karyawan Bank Di Kota Palembang - Sheren Felicia; Lienny Cia; Alnov Martin (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the influence of cyberloafing and job stress on employee performance among bank employees in Palembang City. The research adopts a quantitative empirical approach using a survey method to test causal relationships among variables based on numerical data obtained from respondents. Data were collected through an online questionnaire distributed to bank employees who met predetermined purposive sampling criteria. The analysis employed multiple linear regression supported by classical assumption testing, partial significance testing (t-test), simultaneous testing (F-test), and coefficient of determination analysis. The results reveal that cyberloafing has a positive and significant effect on employee performance. Conversely, job stress demonstrates a negative and significant influence on employee performance, suggesting that excessive work pressure reduces productivity and overall task effectiveness. These findings highlight the importance of balanced digital behavior management and effective stress management strategies in enhancing employee performance within technology-driven organizational environments.